Adoption intensity of soil and water conservation techniques in Burkina Faso is influenced by farmers’ preferences for their attributes - Hadji Adama Ouédraogo; Youmanli Ouoba (Scientific Reports)
Abstract Soil degradation is a major cause of agricultural productivity decrease in sub-Saharan Africa. In Burkina Faso, efforts to reduce this environmental issue has emerged since several decades. However, most of the techniques developed are rarely adopted by farmers. In addition, those adopted are on small areas. This study aims to analyze the effect of farmers’ preferences for soil and water conservation techniques’ attributes on their intensity of adoption. Cross-sectional data was collected from 335 farmers in four rural municipalities in Burkina Faso, using a discrete choice experiment approach. The standard Tobit model was used for data analysis. Results showed that soil and water conservation techniques’ attributes as runoff reduction, soil fertilization and soil restoration explained farmers’ decision to adopt and intensify the adoption of these techniques. In addition, location in the northern sudanian agroecological zone, access to extension services and education influenced positively soil and water conservation techniques’ adoption intensity. However, equipment, labor and cash constraints decrease these techniques’ adoption intensity. These results suggest that incentives for the adoption and intensification policies should be oriented toward farmers’ capacities to produce quantity and quality organic fertilizers reinforcement, build an industrial unit to transform household waste into organic manure for agricultural use.